COMPUTATIONAL APPLICATION OF THE STOCHASTIC DIFFERENTIAL EQUATIONS - Raffo Lecca, Eduardo (2006)
Numeric methods are effective tools to solve science or engineering problems , which use deterministic differential equations. We have Euler’s and Heun’s methods and Runge- Kutta’s schemes. Unfortunately, these algorithms don’t work with stochastic differential equations. The main application is referred to the utilization of stochastic calculus in the financial area. The Black-Scholes and Merton model of the price values option in the financial markets is expressed by the Brownian movement and the stochastic differential equation, proposing the financial derivatives valorization by means of the stochastic calculus.